Collaborative Governance in the Management of Integrated Community Shelters Post Disaster (ICS) in the City of Palu - Daswati, Daswati; Samad, Muhammad Ahsan; Wekke, Ismail Suardi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This article tells the involvement of humanitarian organizations in the post-war reconstruction process of disaster in the city of Palu, Sigi and Donggala Regencies. The presence of humanitarian organizations is urgently needed to help the process of acceleration of reconstruction. In carrying out its humanitarian mission, it is expected that these institutions are coordinated by the authority of the government/state. Management of Integrated Community Shelter expected able to help the process of reconstruction post disaster apparently also still constrained in the pattern of coordination. Coordination pattern which is less likely to occur in delivering open and funneling aid to victims. this paper found that the existence of the weakness of the State in controlling and embody the humanitarian agency's involvement in the process of reconstructions. Collaborative approach to governance in the management of Integrated Community Shelter appears as an alternative solution in the answer to these problems.